Risk Factors of First Febrile Seizures Admitted in a Tertiary Care Hospital (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Febrile seizure (FS) is the most common convulsive event in children. It is the most common type of seizure that every pediatrician has to deal with. However, the etiology of febrile seizure is still unclear. The present study was intended to identify the risk factors of first febrile convulsion among 6 months to 5 years old children.Materials & Methods: A case-control study was carried out on a total of 200 children-100 cases (children with febrile convulsion) & 100 controls (without febrile convulsion) selected from the In-patient Department of Dhaka Shishu Hospital over a period of six months between May 2012 to October 2012. Data were collected on variables of interest using a semi-structured research instrument. The Chi-square test and Odd Ratio were employed to compare the risk factors between case and control groups.Result: There was no association of febrile seizure with age of the children, but males were more often associated with FS than the females with risk of developing febrile seizures in boys was 3.5-fold (95% CI=1.8 -6.8) higher than that in girls (p